The Effect Of Guided Inquiry Learning Model On Student Learning Outcomes On Chemical Equilibrium Material XI Grade High School - Rosanna, Desi Lisa; Harahap, Laily Wardani (LAVOISIER: Chemistry Education Journal, 2025)
This study aims to determine the effect of guided inquiry learning model on student learning outcomes in hydrocarbon material class XI. This type of research is a quasi-experiment. The population in this study was the entire class XI MAN South Tapanuli. Sampling was done by random sampling. Class XI MIA 1 using guided inquiry learning model and class XI MIA 2 using conventional learning model. . The instrument used is a test of learning outcomes in the form of multiple choice consisting of 20 items. Obtained post-test results with an average of 71.71 experimental class and 61.43 control class. Based on the t test obtained th tt which is 3.9691.997. Indicates the influence due to differences in student learning outcomes using guided inquiry learning models better than conventional learning models on the subject matter of chemical equilibrium class XI.